Use of resuscitative endovascular balloon occlusion of the aorta in ruptured pseudoaneurysm after simultaneous pancreas-kidney transplantation - Lindsay A. Kohan, BS, BA; Rishi Kundi, MD; Lucas Sjeklocha, MD; Daniel Haase, MD; Silke V. Niederhaus, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a temporizing measure for severe, acute hemorrhage until definitive treatment. REBOA has demonstrated utility in the trauma setting, but never in transplant-related complications. We report a case of a ruptured pseudoaneurysm two weeks after simultaneous pancreas-kidney transplant complicated by hemorrhagic shock with REBOA utilization allowing for hemorrhage control before emergent pancreas graft explant. The patient had a successful operation and is recovering well. There is sparse literature describing the use of REBOA in nontraumatic hemorrhage, but this represents the successful use in a transplant-related complication.